(untitled) (Annals of the University of Bucharest. Political Science Series, 2025)
As of 2022, there has been little research done on the Romanian examples of participatory budgeting. This paper aims to provide an overview of the evolution of participatory budgeting in Romania, focusing on a descriptive analysis of how this particular form of participatory politics has been implemented in the country. To this end, we look at the 11 Romanian cities where participatory budgeting programs have been put in place, how these programs are financed compared to local budgets, and what instruments of interfacing with and involving the wider public were used in each case. This analysis is done using data collected from each city’s participatory budgeting platform.